Atmospheric water‐vapour profiling from passive microwave sounders over ocean and land. Part II: Validation using existing instruments. (11th May 2012) - Bernardo, Frédéric; Aires, Filipe; Prigent, Catherine
Abstract In a companion article (Paper I), a water‐vapour retrieval algorithm has been developed using microwave sounding observations. An operational chain derived from this algorithm is being used for the Megha‐Tropiques mission, launched in autumn 2011. The water vapour is retrieved for clear and cloudy scenes, excluding precipitation cases, over ocean and land surfaces. By‐products are also calculated by the algorithm, including surface temperature and microwave emissivities over land. Evaluation of the water‐vapour products is the main objective of this article. The algorithm is tested using the HSB/AMSR‐E (resp. MHS/AMSU‐A) instruments on board the AQUA (resp. MetOp) platform, over the Tropics between ±30° in latitude. Results are compared with European Centre for Medium‐Range Weather Forecasts (ECMWF) analyses and data from radiosondes. The root‐mean‐square error for the total column water vapour is ∼5 kg m2 for both clear and cloudy scenes, compared with radiosondes over land. The atmospheric water‐vapour profile is retrieved for six atmospheric layers and the root‐mean‐square error is estimated to be lower than 20% in relative humidity, even for the lowest atmospheric layer over land. A posteriori validation tests on the brightness temperatures indicate an overall positive impact of the retrievals relative to a priori ECMWF analyses. Copyright © 2012 Royal Meteorological Society